Literasi Digital Dalam Meningkatkan Hasil Belajar Fikih Siswa Kelas XI Agama Materi Pernikahan Dalam Islam MAN Model 1 Manado - Alkatiri, Rahmawaty (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2024)
This research is Classroom Action Research (PTK). The research subjects were students of class XI Religion MAN Model 1 Manado. The population in this study were students of class XI Religion MAN Model 1 Manado. The number of students in class ), and 4) Reflection Stage (Reflecting). The use of digital literacy in research refers to or adapts the demonstration learning method with the Explicit Instruction learning model. The improvements made by the researcher in cycle II provided an increase in student learning outcomes so that there was 1 student remaining who had not achieved a completeness score in learning Islamic jurisprudence material on marriage with a normalized gain calculation value = 0.25 in the low category and a percentage increase in learning outcomes of 80% to 96 % of students who achieved a completion score. In other words, there has been an increase in student learning outcomes in learning Islamic jurisprudence material on marriage by using digital literacy.